The Frequency and the Effects of 21-Hydroxylase Gene Defects in Congenital Adrenal Hyperplasia Patients - BEREKET, ABDULLAH; GÜNEY, AHMET İLTER; EREN, FATİH; ULUCAN, KORKUT; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (WILEY, 2014)
Congenital adrenal hyperplasia (CAH) is a group of genetic endocrine disorders, caused by enzyme deficiencies in the conversion of cholesterol to cortisol. More than 90% of the cases have 21-hydroxylase deficiency (21-OHD). The clinical phenotype of the disease is classified as classic, the severe form, and nonclassic, the mild form. In this study, it was planned to characterize the mutations that cause 21-OHD in Turkish CAH patients by direct sequencing and multiplex ligation-dependent probe amplification (MLPA) analysis and to investigate the type of CAH (classic or nonclassic type) that these mutations cause. A total of 124 CAH patients with 21-OHD and 100 healthy volunteers were recruited to the study. Most of the mutations were detected by direct sequencing. Large gene deletions/duplications/conversions were investigated with MLPA analysis. Results were evaluated statistically. At the end of our study, 66 different variations were detected including SNPs and deletions/duplications/conversions. Of these variations, 18 are novel, of which three cause amino acid substitutions. In addition, 15 SNPs which cause amino acid changes were identified among these variations. If similar results are obtained in different populations, these mutations, in particular the novel mutation 711 G>A, may be used as markers for prenatal diagnosis.
Keywords: CYP21A2; CAH; 21-OHD; direct sequencing; MLPA analysis; PRENATAL-DIAGNOSIS; MOLECULAR DIAGNOSIS; CYP21A2 GENE; CLASSIC FORM; DEFICIENCY; MUTATIONS; IDENTIFICATION; REARRANGEMENTS; PHENOTYPE; GENOTYPE